Food lit a reader's guide to epicurean nonfiction - Stoeger, Melissa Brackney (Real stories, 2013)
"An essential tool for assisting leisure readers interested in topics surrounding food, this unique book contains annotations and read-alikes for hundreds of nonfiction titles about the joys of comestibles and cooking"-- Provided by publisher.